Early childhood education: perceptions, problems and possibilities - Little, Jennifer Leslie (1997)
This thesis attempts to provide evidence, based in historical and contemporary research, of the importance of early years education, not only in terms of academic achievement, but of social outcomes as well; to examine the perceptions of teachers in relationship to societal influences and the effects of such on the changing educational needs of the child; and to suggest possible elements for high quality programme development in the early years.